2000
DOI: 10.1038/35008030
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of atoms across a surface at room temperature

Abstract: Since the realization that the tips of scanning probe microscopes can interact with atoms at surfaces, there has been much interest in the possibility of building or modifying nanostructures or molecules directly from single atoms. Individual large molecules can be positioned on surfaces, and atoms can be transferred controllably between the sample and probe tip. The most complex structures are produced at cryogenic temperatures by sliding atoms across a surface to chosen sites. But there are problems in manip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 21 publications
0
40
0
Order By: Relevance
“…Most of the work on the construction of complex structures [7,8] has been performed at cryogenic temperatures using systems where the interaction between the adsorbate and the surface is weak, allowing the atoms to be manipulated with a weak tip-adatom interaction. Bromine on copper (100) is of great interest as a system where controlled room temperature nanomanipulation has been achieved [9]. An understanding of systems such as this one is essential if we are to suceed in "manufacturing" nanoscale devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the work on the construction of complex structures [7,8] has been performed at cryogenic temperatures using systems where the interaction between the adsorbate and the surface is weak, allowing the atoms to be manipulated with a weak tip-adatom interaction. Bromine on copper (100) is of great interest as a system where controlled room temperature nanomanipulation has been achieved [9]. An understanding of systems such as this one is essential if we are to suceed in "manufacturing" nanoscale devices.…”
Section: Introductionmentioning
confidence: 99%
“…The first is identification of the adsorption site. It is generally believed that Br on Cu(100) must occupy fourfold hollow sites as shown in figure 1, but a surprising result of the STM experiments is that the topographic features assigned to adsorbed bromine atoms appear in registry with the greyscale maxima of the STM images [9,10] (figure 2). This registry is preserved under a wide range of differing tip conditions which lead to imaging the bromine induced features as greyscale maxima, minima or Mexican hat sombreros [10].…”
Section: Introductionmentioning
confidence: 99%
“…In mechanical-induced manipulation, the attractive and repulsive interaction forces between the probe tip and the target object are used to drive the motion [16][17][18][19][20] . In contrast, in electron-induced manipulation the atom or molecule is excited by the inelastic tunnelling electron and hence they start to diffuse themselves [21][22][23][24] . In both modes, manipulation at RT requires a delicate balance between a high enough initial binding energy to the substrate to avoid desorption and a small enough diffusion barrier to be able to be influenced by the local probe tip.…”
mentioning
confidence: 99%
“…Extensive SPM studies have reported a variety of methods for single-atom/ molecule manipulation that are mediated by several tip-sample interactions 1,2,28,29 . We used a combined AFM/STM to fabricate and operate an atomic-scale switch at RT, which enables individual interactions during each manipulation process to be directly monitored.…”
Section: Resultsmentioning
confidence: 99%